A practical and concise homogeneous nickel catalyst for efficient solvent-free synthesis of γ-valerolactone. Issue 11 (21st May 2020) - Zada, Bakht; Zhu, Rui; Wang, Bing; Liu, Jiao; Deng, Jin; Fu, Yao
Abstract : An inexpensive and readily available nickel-phosphine catalyst is used to efficiently catalyze the reduction of levulinic acid to produce γ-valerolactone and the catalyst cost only needs a few nickel coins (<0.1 $ per kg GVL). Abstract : Here, we report an inexpensive nickel-phosphine complex that can catalyse neat levulinic acid (LA) to γ-valerolactone (GVL) without additive at 1 atm H2, and the catalyst can be reduced to 0.01 mol% at 30 atm. 5.8 kg LA was successfully converted to GVL in a yield of 94% with 0.1 mol% catalyst. DFT calculations and in situ APXPS indicate that L–Ni + –H species are the key active intermediates.